Concise Review: Drug Discovery in the Age of the Induced Pluripotent Stem Cell. (3rd February 2014) - Ko, Huaising C.; Gelb, Bruce D.
Abstract : The growing number of human disease models made with patient-specific induced pluripotent stem cells (iPSCs) has made it possible to conduct research on a wide range of disorders. This review surveys the incorporation of iPSC technology into drug therapy development, which holds promise as a powerful and nuanced approach to personalized medicine. Abstract: For decades, the paradigm of drug discovery and development has relied on immortalized cell lines, animal models of human disease, and clinical trials. With the discovery of induced pluripotent stem cell (iPSC) technology in 2007, a new human in vitro drug testing platform has potentially augmented this set of tools by providing additional ways to screen compounds for safety and efficacy. The growing number of human disease models made with patient-specific iPSCs has made it possible to conduct research on a wide range of disorders, including rare diseases and those with multifactorial origin, as well as to simulate drug effects on difficult-to-obtain tissues such as brain and cardiac muscle. Toxicity and teratogenicity assays developed with iPSC-derived cells can also provide an additional layer of safety before advancing drugs to clinical trials. The incorporation of iPSC technology into drug therapy development holds promise as a more powerful and nuanced approach to personalized medicine.